2012
DOI: 10.4049/jimmunol.1200262
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule-Epidermal Growth Factor-Factor 8 Attenuates Neutrophil Infiltration in Acute Lung Injury via Modulation of CXCR2

Abstract: Excessive neutrophil infiltration to the lungs is a hallmark of acute lung injury (ALI). Milk fat globule-EGF factor 8 (MFG-E8) was originally identified for phagocytosis of apoptotic cells. Subsequent studies revealed its diverse cellular functions. However, whether MFG-E8 can regulate neutrophil function to alleviate inflammation is unknown. We therefore aimed to reveal MFG-E8 roles in regulating lung neutrophil infiltration during ALI. To induce ALI, C57BL/6J wild-type (WT) and Mfge8−/− mice were intra-trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 43 publications
6
89
0
1
Order By: Relevance
“…We have previously found no differences in lung inflammation in bleomycin-treated Mfge8 −/− mice (29). Other studies have shown that Mfge8 −/− mice develop exaggerated lung inflammation after intratracheal LPS instillation or after reperfusion injury secondary to intestinal ischemia (42,43). Given the important role of the immune system in asthma, we were curious to determine whether there would be differences in airway inflammation in Ova-challenged Mfge8 −/− mice.…”
Section: Discussionmentioning
confidence: 93%
“…We have previously found no differences in lung inflammation in bleomycin-treated Mfge8 −/− mice (29). Other studies have shown that Mfge8 −/− mice develop exaggerated lung inflammation after intratracheal LPS instillation or after reperfusion injury secondary to intestinal ischemia (42,43). Given the important role of the immune system in asthma, we were curious to determine whether there would be differences in airway inflammation in Ova-challenged Mfge8 −/− mice.…”
Section: Discussionmentioning
confidence: 93%
“…50 In lipopolysaccharide-induced acute ALI, gene-targeted mice lacking MFG-E8 showed increased neutrophil infi ltration, increased infl ammatory cytokines, and decreased survival. 51 Resolvin E1 enhances apoptosis and uptake of human neutrophils induced by microbe ingestion and reduced lung infl ammation in three murine models. 52 Conversely, instillation of apoptotic cells into the lungs of mice following bleomycin lung injury reduced infl ammatory cytokine production and lung fi brosis via hepatocyte growth factor-dependent mechanisms, resulting in increased survival.…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…Также внутрибрюшинное введение мышам экзогенного опсонина -факто-ра 8 эпидермального фактора роста, ассоциирован-ного с глобулой молочного жира (milk fat globule-EGF factor 8 protein -MFG-E8), способствующего эффероцитозу, сопровождается снижением уров-ня продукции провоспалительных цитокинов в ткани легких, уменьшением объема поражения легких и уровня летальности экспериментальных мышей [19]. С другой стороны, при остром LPS-индуцированном поражении легких мышей с нока-утным геном Mfg-E8 наблюдаются высокая степень инфильтрации нейтрофилами очага поражения лег-ких, более высокий уровень провоспалительных ци-токинов и низкий уровень выживаемости экспери-ментальных животных [7]. Также введение TNF-α сопровождается подавлением активности клиренса апоптотических клеток из легких и, вероятно, ассо-циированным с данным феноменом увеличением уровня воспаления легких [12].…”
Section: эффероцитоз как основной механизм физиологического снижения unclassified